Structural changes of the stromal and vascular components of n.tibialis in the case of diabetes mellitus - O. V. Besedinska (Zaporozhye State Medical University, 2013)
Introduction Diabetic microangiopathy is a complex of pathologic changes in the vessels of the haemomicrocirculatory blood stream and in the perimicrovascular zones, which develop under diabetes mellitus. However, the structural changes in the vessels of peripheral nerves under diabetes mellitus are insufficiently highlighted in professional literature, and thus become the object of the present study. Objective of the research The objective of the research is to study the structural changes in the stromal and vascular components of n.tibialis under diabetes mellitus. Materials and methods Morphological research of the tissues of n.tibialis of patients with diabetes mellitus was carried out. 192 cases were studied, among them 96 (50%) of autopsy material and 96 (50%) of operational material (tissues of the amputated lower extremities of patients diagnosed with "diabetic foot"). Each n.tibialis was studied separately in its lower, middle and upper segments. Research results and their discussion All cases under study were divided into four groups. The first group included 30 cases (15,63%) with the initial manifestation of diabetic microangiopathy in individual arteriolae and capillaries. Venulae were hyperemic. Connective tissue surrounding the vessels was swollen, with slight lymphocytic infiltration. No structural changes in the stromal component, except perivascular oedema, were detected. The second group consisted of 49 patients (25,52%) with the symptoms of moderate diabetic microangiopathy. Microscopic research showed that in addition to the changes characteristic for initial diabetic microangiopathy hyalinosis of segmental character manifested in these patients. Plasmatic saturation was spread over the whole vascular wall. Venular wall was deformed, sometimes with aneurismal prominence. Perivascular enlargement of connective tissue was observed. Structural changes in the stromal component were observed in the lower segment of n.tibialis, specifically the symptoms of oedema of endo-, peri- and epineurium were registered. The third group included 82 cases (42,71%) with the symptoms of moderate diabetic microangiopathy. Cell proliferation in the vascular wall was minimal or even absent totally. The walls of the affected vessels were almost completely replaced by hyaline. Sclerosis progressed in endo-, peri- and epineurium of the lower segment, partial epineurium detachment was observed. Interstitial edema was registered in the middle segment. The fourth group consisted of 31 cases (16,14%) with marked diabetic microangiopathy. Histologically, only solitary endotheliocytes were registered in the affected capillaries and arteriolae in all the segments of n.tibialis, while the thickened vascular wall was completely replaced by hyaline masses immensely narrowing vascular lumen, at times to its total obliteration. Venulae were dilated and deformed. Interstitial edema was spread over the upper segment of n.tibialis. Sclerosis was observed in the lower and middle segments, with partial epineurium detachment in the middle segment, and epi- and perineurium detachment in the lower one. Conclusions: Structural changes in the stromal component of n.tibialis under diabetes mellitus are spread from the distal to the proximal nerve segment, and are manifested in sclerosis and interstitial edema, which first appear in the epineurium, are gradually expanded to peri- and endoneurium, and lead to gradual epi- and perineurium detachment. Under diabetes mellitus structural changes are observed in all sections of the haemomicrocirculatory blood stream of peripheral nerves; they are manifested in arteriolae and capillaries in plasmatic saturation, in thickening of basal membranes and hyalinosis of vascular walls, in proliferation of endotheliocytes, pericytes, myocytes, all characteristic for diabetic microangiopathy; in venulae these changes are manifested in widening and the appearance of aneurismal dilation. Prospects of further research The prospects of further research in this field lie in the study of molecular mechanisms affecting the haemomicrocirculatory blood stream of peripheral nerves under diabetes mellitus.